Transformada Wavelet na detecção de patologias da laringe - Carvalho, Raphael Torres Santos (2012)
The amount of non-invasive methods of diagnosis has increased due to the need for simple, quick and painless tests. Due to the growth of technology that provides the means for extraction and signal processing, new analytical methods have been developed to help the understanding of analysis of the complexity of the voice signals. This dissertation presents a new idea to characterize signals of healthy and pathological voice based on one mathematical tools widely known in the literature, Wavelet Transform (WT). The speech data were used in this work consists of 60 voice samples divided into four classes of samples: one from healthy individuals and three from people with vocal fold nodules, Reinke’s edema and neurological dysphonia. All the samples were recorded using the vowel /a/ in Brazilian Portuguese. The obtained results by all the pattern classifiers studied indicate that the proposed approach using WT is a suitable technique to discriminate between healthy and pathological voices, since they perform similarly to or even better than classical technique, concerning recognition rates.